Static Load Test interpretation methods of pile base capacity approximation for design of wind turbine deep foundation. (August 2020) - Baca, M
Abstract: The bearing capacity of a pile is mainly assessed from a static load test, which is widely considered as the most reliable method of pile testing. The test provides important information about pile behaviour in a subsoil, but often for more precise data it should be performed on additionally instrumented piles. With specially prepared pipe piles static load tests can be performed with a load applied only to a pile base. The results of this test allow on an evaluation only of pile base bearing capacity, although it often requires an application of some of the methods dedicated to analyse the static load test results. In paper some of the methods for evaluation bearing capacity of a pile from a static load test are introduced. Evaluation of pile base bearing capacity by different methods was compared using results of static load tests with a load applied only to the pile base. A discussion of results and future recommendations were also presented.